Assessment of the quality of honey of various botanical and geographical origins based on the pollen spectrum and physico-chemical properties. - Ksentini, Hana; Meddad-Hamza, Amel; Hamel, Tarek; Bellili, Abdelmalek; Babali, Brahim; Boutabia, Lamia; Salvo-Tierra, Ángel Enrique; Picornell Rodríguez, Antonio (Národné Poľnohospodárske a Potravinárske Centrum, 2024)
Authenticity of honey presents significant challenges to food quality control, necessitating continuous modernization and enhancement of analytical methodologies. This study aimed to characterize 24 honey samples collected from eight regions in northeastern Algeria by analysing their physico-chemical parameters and pollen profiles. The results revealed significant pollen diversity across all samples, predominantly monofloral honeys, particularly eucalyptus honey, along with Hedysarum coronarium L., Arbutus unedo L., Lavandula stoechas L., Ziziphus lotus (L.) Lam. and Citrus sp. Multifloral honeys contained pollen from diverse taxa including Eucalyptus camaldulensis Dehnh., Hedysarum coronarium L., Echium plantagineum L., Lavandula stoechas L., Raphanus raphanistrum L. and Malva sylvestris L., common to northeastern Algeria's ecosystems. Most honey samples met international physico-chemical standards, indicating high quality. However, honey quality is predominantly influenced by its botanical origin, as demonstrated by principal component analysis, cluster analysis and co-inertia analysis, which grouped the samples into seven distinct physico-chemical units. Precise characterization is essential for enhancing local honey production by elucidating the complex relationships between pollen composition, botanical origin and physico-chemical properties.
Authors may self-archive an authorial version of their article on their own website and their institution’s repository, including the final version. Furthermore, the author’s version may only be posted provided that reference is given to the original source of publication.
Keywords: Palinología; Miel - Calidad; Honey; Melissopalynology; Physico-chemical property; Quality; Geographical provenance; Northeastern Algeria